Improving acute demyelinating lesion detection: which T1-weighted magnetic resonance acquisition is more sensitive to gadolinium enhancement? - Lázaro Luiz Faria do AMARAL; Diego Cardoso FRAGOSO; Antonio José da ROCHA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Because of the need for a standardized and accurate method for detecting multiple sclerosis (MS) inflammatory activity, different magnetic resonance (MR) acquisitions should be compared in order to choose the most sensitive sequence for clinical routine. Objective To compare the sensitivity of a T1-weighted image to a single dose of gadolinium (Gd) administration both with and without magnetization transfer to detect contrast enhancement in active demyelinating focal lesions. Methods A sample of relapsing-remitting MS patients were prospectively examined separately by two neuroradiologists using a 1.5 Tesla scanner. The outcome parameters were focused on Gd-enhancement detection attributed to acute demyelination. All MR examinations with at least one Gd-enhancing lesion were considered positive (MR+) and each lesion was analyzed according to its size and contrast ratio. Results Thirty-six MR examinations were analyzed with a high inter-observer agreement for MR+ detection (k coefficient > 0.8), which was excellent for the number of Gd-enhancing lesions (0.91 T1 spin-echo (SE), 0.88 T1 magnetization transfer contrast (MTC) sequence and 0.99 magnetization-prepared rapid acquisition with gradient-echo (MPRAGE). Significantly more MR+ were reported on the T1 MTC scans, followed by the T1 SE, and MPRAGE scans. Confidently, the T1 MTC sequence demonstrated higher accuracy in the detection of Gd-enhancing lesions, followed by the T1 SE and MPRAGE sequences. Further comparisons showed that there was a statistically significant increase in the contrast ratio and area of Gd-enhancement on the T1 MTC images when compared with both the SE and MPRAGE images. Conclusion Single-dose Gd T1 MTC sequence was confirmed to be the most sensitive acquisition for predicting inflammatory active lesions using a 1.5 T magnet in this sample of MS patients.